Peculiarities of specialized enterprises and organizations activity in competitiveness improvement context - Naumik-Gladka, Kateryna; Tkatsevych, Kateryna; Наумік-Гладка, К. Г.; Ткацевич, К. А. (Харківський національний автомобільно-дорожній університет, 2016)
The key concept of this article is characterized by the analyses of the main features of activity of specialized tourism enterprises. The goal is to identify the modern classification criteria for the business entities in the market of tourist services and clarify the peculiarities of the activity of municipal organization in the tourism market of Ukraine. The comparative characteristics are given and the classification for business entities in the tourism sector at the national level is designed. The sphere of activity of municipal enterprises in tourism industry on the local market was observed by the authors. The obtained results may be implemented in the organization and planning of the tourism strategies on the local and governmental levels. The conclusions of the article are the approval of that such organizational form of the enterprise's activity as a municipal organization can be characterized as a monopolistic structure in the Kharkiv market. Profits come to the government budget and it influences positively on the whole situation in the service sector of Ukraine. It also helps to support tourism industry and tourist flows in Ukraine. The complex approach for the organization of activity of business entities can be characterized as a positive one, as the business activity of such entrepreneurship has a very high level of competitiveness on the market. This issue was also investigated and proved by the authors in this article.
Особливості діяльності спеціалізованих підприємств і організацій в контексті підвищення конкурентоспроможності
Keywords: tourism enterprise; organization of activity; classification; municipal enterprise; туристичне підприємство; організація діяльності; класифікація; муніципальні заклади; 658.11